Development aid in fragile states: Investigating the effectiveness of COVID-19 aid in the Democratic Republic of the Congo - Hany Besada; Lukmon Akintola (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Drawing from a growing body of literature on development aid in fragile contexts, this paper investigates the effectiveness of COVID-19 aid in the Democratic Republic of the Congo (DRC). The paper uses the OECD's Principles for Good International Engagement in Fragile States and Situations to critically evaluate the effectiveness of several types of health and nonhealth COVID-19 aid that donor agencies provided to the DRC and their impact on the country's socio-economic stability. Beyond identifying the gaps and strength of the COVID-19 aid to the DRC, this paper also leverages the OECD Principles to present recommendations to improve the effectiveness of development aid to the country and other fragile contexts.
Keywords: 330; COVID-19; OECD; development aid; fragile states; the Democratic Republic of the Congo